Ethnobotanical study of medicinal plants utilized by the Baduy tribe used as a learning resource - Khastini, Rida Oktorida; Wahyuni, Indria Wahyuni; Saraswati, Irma; Alimuddin, A.; Nuangchalerm, Prasart (JPBI (Jurnal Pendidikan Biologi Indonesia), 2019)
The existence of contextual learning resources has been known to be able to improve the meaningful learning, particularly biology learning. This research provides the information about the medicinal plant utilized by the Baduy tribe as well as its endeavour in developing the results obtained as a contextual-based module. This research and development was designed using Thiagarajans’ model, which was limited in three phases (define, design, and development). The data was collected using interview guideline, validation sheets, and students' response questionnaires. The research findings inform that there were 67 species utilized by the Baduy tribe as the medicinal plants. These species belong to Spermatophyte and divided into 31 families. Furthermore, the validation results showed that the media developed was valid; in which the best component of module, based on students' response, was its presentation (the mean value was 89.5%). It can be concluded that the media developed is feasible to use as a learning resource.